The Adaptability and Innovation Capacity of Small and Medium Construction Companies to Information and Computers Technology in the Developing Countries - Bahaswan, Rizal; Rosyid, Amrun; Machicky Mayestino, Alexander; Eko Guntoro, Dani (Media Komunikasi Dunia Ilmu Sipil (MoDuluS), 2025)
The construction industry in developing countries is undergoing a pivotal transformation, driven by the integration of information and communication technology (ICT). This study investigates how ICT adoption influences the adaptability and innovation capabilities of small and medium-sized enterprises (SMEs) within this sector. Employing a mixed-methods approach, the research combines quantitative data from 50 construction SMEs across chosen regions in Indonesia, with qualitative insights from 15 in-depth interviews. Findings reveal that ICT significantly enhances both adaptability and innovation performance. Notably, adaptability serves as a key mediating factor, linking ICT usage to innovative outcomes. Technologies such as mobile-based project coordination tools, cloud platforms, and Building Information Modeling (BIM) were found to improve operational responsiveness and foster novel approaches in project execution and service delivery. However, the study also identifies critical contextual challenges—including limited infrastructure, cost barriers, and cultural resistance—that hinder widespread ICT integration. The research contributes to theory by extending the Technology-Organization-Environment (TOE) framework to include adaptability as a mediating construct. Practically, it offers policy and managerial recommendations for enabling digital transformation in resource-constrained construction environments. Ultimately, the study underscores the strategic potential of ICT to enhance resilience and competitiveness among construction SMEs, provided that adoption is contextually supported and strategically implemented.